Communicating sustainability: student perceptions of a behavior change campaign. Issue 1 (3rd January 2017) - Godfrey, D. Matthew; Feng, Patrick
Abstract : Purpose: This paper aims to investigate the impacts of a science-based environmental communication campaign at a university dining hall. The impacts are assessed in terms of student attitudes toward sustainability, food consumption choices and perceptions and understanding of the campaign and the information it communicated. Design/methodology/approach: A communication campaign was designed to convey the water footprint of food entrées available at a university dining hall. This campaign was tested during a three-week field experiment in which students at the dining hall were exposed to information about the sustainability of their food. To measure behavior and attitude change, sales and production data were collected before, during and after the campaign, and pre- and post-test surveys were administered. To better understand perceptions, the authors conducted in-depth interviews with undergraduate students who frequented the dining hall. Findings: Consumption patterns did not change significantly as a result of the campaign, and students' attitude scores actually became slightly less positive toward choosing low water footprint foods. Interview data helped explain these results by showing that the ability and desire of students to choose sustainable food were overwhelmed by convenience and time pressures; other food attributes often outweighed sustainability; limited food source information could not verify the benefits of sustainable food; and the science of water footprints was disconnected from students' subjective concepts of sustainability. Originality/value: This paper empirically examines how students understand and interpret an environmental change campaign focused on sustainable food. It addresses an important gap in the literature by augmenting experimental and survey results with in-depth interview data, which help explain the often ineffective outcomes of behavior change campaigns. The research was conducted in the novel setting of a university dining hall.